Generating pure spin current with spin-dependent Seebeck effect in ferromagnetic zigzag graphene nanoribbons. (23rd May 2019) - Zhou, Yanhong; Zheng, Xiaohong
Abstract: Pure spin current is of great importance in spintronics and may be achieved by spin dependent Seebeck effect (SDSE) in magnetic systems. Zigzag-edged graphene nanoribbons (ZGNRs) are very well-known 2D magnetic nanostructures. However, perfect and pristine ZGNRs either in the anti-ferromagnetic ground state or in the ferromagnetic (FM) state are not capable of producing pure spin current by SDSE at low temperature. In this work, by density functional theory calculations, we propose a scheme for generating pure spin current using SDSE in FM-ZGNRs by introducing antidots. Specifically, by creating a hexagonal antidot with either armchair edges or zigzag edges in the scattering region, we can get finite Seebeck thermopower for both spin channels with opposite signs, leading to the opposite flow directions of the two spin channels. The mechanism is well explained by the cooperation of the varying localization features of states around the Fermi level and the antidot induced scattering potential. By slightly tuning the chemical potential, pure spin current can be achieved. The size and edge shape effects have also been systematically studied. The findings indicate a novel scheme for thermally generating pure spin current in zigzag graphene nanoribbons and may find important application in graphene based spintronics.